INDUKSI KALUS KLON KAKAO (THEOBROMA CACAO L) SULAWESI 2 PADA MEDIUM MS DENGAN PENAMBAHAN 2,4-D, BAP DAN AIR KELAPA - Urfiana, Urfiana; Haliana, Haliana; Muslimin, Muslimin; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2013)
Sulawesi 2 cacao clone is one of the clones which grown by local farmer in Central Sulawesi. One problem in cacao development in this time is the availability of high quality of seeds. One posible way in overcoming of this problem is through the application of tissue culture techniques via embryogenesis. The early stages of embryogenesis is callus induction, which aim to get emryonic callus cells and it can be a model in cacao research. This study was conducted over March and June 2013 in the Tissue Culture Laboratory, Faculty of Forestry Tadulako University. Explant that used was Stamen of flower of Sulawesi 2 cacao clone. This experiment was based on a complete randomized design (CRD) with 4 treatments, and it were repeated 3 times. On every single unit was growth 10 of explants. Different medium as treatments tested were: MS0 + 2 ppm 2,4-D + (15%) Coconut water (MK1), MS0 + 2 ppm 2,4-D + 0.2 ppm BAP + (15%) Coconut water (MK2) , MS0 + 3 ppm 2,4-D + (15%) coconut water (MK3), ms0 + 3 ppm 2,4-D + 0.2 ppm BAP + (15%) coconut water (MK4). Callus development were observed based on the emergence of callus, the percentage of explants producing callus, and cell callus morphology. Callus induction was done under dark condition and  temperature of 26º C. The results showed that all of the tested treatments can induce the callus of cacao. The best medium was MS medium + 3 ppm 2,4-D + (15%) Coconut water (MK3), characterized by the appearance of white, callus in intermediate-type, the callus mass was relatively larger than its under others treatments. Under this treatment, explant can produce uniform-relatively big cell and active in proliferation in 10 days after culture